THE ROLE OF THE YOUNGER GENERATION IN PARTICIPATORY SUPERVISION GENERAL ELECTION IN 2024 - Tobing, Rudyanti Dorotea; Astutik, Sri (Awang Long Law Review, 2023)
The purpose of this research is first to describe the implementation of the 2024 General Election and, secondly, to describe the role of the younger generation in participatory supervision of the 2024 General Election. The normative legal research method uses legal materials as the main source, carried out using the philosophical, statute, conceptual, and historical approaches. The research results show that the 2024 general election will be the same as the 2019 election, namely that the legislative and presidential elections (Pilpres) will be held simultaneously. The legal basis for holding the 2024 General Election is the same as the 2019 General Election, namely Law Number 7 of 2017 concerning General Elections (Election Law). The 2024 general election stages begin on June 14, 2022; by Article 167 paragraph (6) of the Election Law, the general election stages begin 20 months before voting day, while voting day is February 14, 2024. Second, supervision of implementing general elections is a desire based on noble concerns (ultimate concerns), to achieve quality general elections. The existence of Bawaslu has experienced significant changes from time to time, which is a sign that its existence is very important for upholding general election justice. The limited number of supervisors is still one of the obstacles for Bawaslu in carrying out supervision at all stages of the general election. The younger generation's involvement in election supervision carried out by Bawaslu is participatory. Participatory supervision is generally described as a joint collective effort involving various components of society to supervise the implementation of general elections. The role of the young generation as participatory observers in general elections is to be able to provide initial information on suspected general election violations, participate in supervising/monitoring the implementation of general elections, prevent general election violations, and report suspected general election violations.